Pelatihan Keterampilan Membuat Informasi Berbasis Video Digital Pada Ikatan Remaja Masjid - Loneli Costaner; Guntoro; Lisnawita (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
Activities in mosques are not only carrying out ritual worship activities, more than that mosques can also print young generations to grow the spirit of organization and creativity. One way to foster the spirit of youth organization is the existence of theMosque Youth Association (IRMAS). Every IRMAS activity will always prepare information, both for event information and useful information to attract the attention of the public, youth and youth to gain knowledge, the information provided can also be a means of da'wah by optimizing on Instagram and YouTube social media. The problems and obstacles for partners are that they do not yet have the ability to create digital video-based information, both for making community profiles, story activities and media promotion of IRMAS activities as well as interesting da'wah facilities so that social media cannot be improved properly. So the solution that can be done is to train partners' skills in making digital video-based information with the kine master android application and training to optimize their social media as a means of information, promotion and da'wah. The method used in this training is lecture and practice, where training participants will be given an understanding of digital video-based information, how to create digital video-based information and applications used to create digital information, such as text processing, image processing, video processing, animation processing. , create community profile lines, create activity storylines, and promotions. The success of the participants can be seen from the results of the training that participants were able to create community profiles and promote IRMAS events, where the level of understanding of participants before training was only 19% and after training participants' understanding increased to 100%. The activities carried out in this community are very much training to help mass organizations in making digital-based information with a success rate of understanding 81%, this percentage is already above 50% which is said to be increasing